2019
DOI: 10.1002/ijch.201800172
|View full text |Cite
|
Sign up to set email alerts
|

Tracking CO Release in Cells via the Luminescence of Donor Molecules and/or their By‐Products

Abstract: Carbon monoxide (CO) is a bioactive signalling molecule that is produced endogenously via the breakdown of heme. Beneficial health effects associated with the delivery of CO gas have spurred the development of CO‐releasing molecules (CORMs) that can be used to provide specific amounts of the gas. In addition to their potential use as therapeutics, CORMs are needed to provide insight into the biological targets of CO. In this regard, light‐activated CO‐releasing molecules (photoCORMs), are valuable for examinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 58 publications
0
35
0
Order By: Relevance
“…The unmasking of the phenolic groups of 3-HF derivatives led to a large Stokes shi, which was previously used for the design of ratiometric uorescent probes. 51 Recently, Berreau and coworkers [32][33][34][35][36] ingeniously found that extended 3-HF derivatives could release CO under visible light irradiation. In this case, the uorescent extended 3-HF moieties were transformed into nonemissive 3-(benzoyloxy)-2-naphthalenecarboxylic acid (3-BNA) species, enabling self-reporting CO release.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The unmasking of the phenolic groups of 3-HF derivatives led to a large Stokes shi, which was previously used for the design of ratiometric uorescent probes. 51 Recently, Berreau and coworkers [32][33][34][35][36] ingeniously found that extended 3-HF derivatives could release CO under visible light irradiation. In this case, the uorescent extended 3-HF moieties were transformed into nonemissive 3-(benzoyloxy)-2-naphthalenecarboxylic acid (3-BNA) species, enabling self-reporting CO release.…”
Section: Resultsmentioning
confidence: 99%
“…S6 †), which is in good agreement with the previous results that 3-HF-based CO donors were relatively stable under dark conditions without premature CO leakage even in an aqueous medium. [32][33][34][35][36] From uorescence spectroscopy, we can observe a remarkable uorescence increase for compound B at 606 nm at the initial 40 s irradiation, corresponding to the deprotection of the 2-nitrobenzyl residue (Fig. S7a †).…”
Section: Photo-triggered Tandem Photochemical Reactions For Co Releasementioning
confidence: 98%
See 3 more Smart Citations